What are the trends and demographics in sports-related pediatric spinal cord injuries? - Nadarajah, V.; Jauregui, J. J.; Perfetti, D.; Shasti, M.; Koh, E. Y.; Henn III, R. F. (The Physician and Sportsmedicine, 2018)
Objectives: Pediatric spinal cord injury (PSCI) is a devastating injury that can cause significant long-term consequences. The purpose of this study is to calculate and report the prevalence of PSCI, identify risk factors for sports-related PSCI, and evaluate associated factors.